Methods of Of Electret Structure Formation - V. A. Sichik; O. A. Ermakova (Наука и техника)
Base methods of electret structure formation are considered on the basis of inorganic dielectric. It is noted that an electret synthesis method using corona discharge is the simplest one in execution and accompanied by high rate of electrization. The advantage of all variants of thermal electrization is high big stability of surface and space charge polarization.